A Semiotic Analysis of the Film KGF Chapter 1 (2018) - R, Rithieshvar (Journal of Advanced Research in Journalism & Mass Communication, 2023)
This research explores the representation of signs, hidden meanings which gives the scene depth that provides the sense of realism to the audience and sentiments where the dialogues touched, the visual representation of set designs, composition, lights, costume, props, colours and everything else in a frame. The research particularly was taken from 2 Kannada-based films. KGF part 1 (2018) and KGF part 2 (2022) by director Prashanth Neel to know about the secret of their commercial success through this art. The director also portrayed the character “Rocky” in impressive way where every youth of the nation lived as this fictional character after watching the film. The result of this study will help the researcher to understand how the signs, signifier and the signified are been placed and presented in this film. How to cite this article: Rithieshvar R. A Semiotic Analysis of the Film KGF Chapter 1 (2018). J Adv Res Jrnl Mass Comm 2022; 9(4): 1-5.